2012
DOI: 10.1103/physrevb.85.235405
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Elliott-Yafet spin-relaxation mechanism in KC8: A model system of biased graphene

Abstract: Temperature-dependent electron spin resonance (ESR) measurements are reported on stage-1 potassium-doped graphite, a model system of biased graphene. The ESR linewidth is nearly isotropic, and although the g factor has a sizable anisotropy, its majority is shown to arise due to macroscopic magnetization. Even though the homogeneous ESR linewidth shows an unusual, nonlinear temperature dependence, it appears to be proportional to the resistivity which is a quadratic function of the temperature. These observatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 44 publications
4
20
0
Order By: Relevance
“…The mean value of the linewidth is 1.28 mT, which is in a good agreement with the literature results: 1.43 mT , 1.14 mT for Bc and 1.26 mT for Bc (), 1.2 mT for Bc, and 1.3 mT for Bc (). This agreement confirms that the sample is indeed the stage‐I KC8 in agreement with the visual identification.…”
Section: Electron Spin Resonance Spectroscopy Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The mean value of the linewidth is 1.28 mT, which is in a good agreement with the literature results: 1.43 mT , 1.14 mT for Bc and 1.26 mT for Bc (), 1.2 mT for Bc, and 1.3 mT for Bc (). This agreement confirms that the sample is indeed the stage‐I KC8 in agreement with the visual identification.…”
Section: Electron Spin Resonance Spectroscopy Resultssupporting
confidence: 91%
“…The temperature was held at 250 C with a gradient of 5 C during the 2‐day long process. Stage‐I stoichiometry was identified by the golden‐yellow color of the samples and by ESR line shape and linewidth . A photograph of the final product can be seen in the inset of Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, it is worth to note that charge neutral bulk graphite also presents a similar line with a linewidth of ≈0.29 and ≈0.51 mT for Bc and Bc, respectively . Since the width is different for the intercalated species: ≈0.26 mT for Li and ≈1.29 mT for K, in a good agreement with previous literature values, thus, a successful bulk intercalation (at least down to the skin‐depth, about 10 μ) is identified. Here, no angular‐dependent measurements can be made, because the boiling ammonia makes the surface curly and ripply.…”
Section: Intercalated Hopg Prepared By the Alkali–ammonia Methodssupporting
confidence: 89%
“…They found that the Elliott-relation is valid with α1 α 2 2 ≈ 10 for alkali metals (except for Li) and for monovalent transition metals (Cu, Ag, and Au). It is interesting to note that the validity of the Elliottrelation has since been confirmed for alkali fullerides 19 and intercalated graphite 20 . Deviations from the Elliott-relation for polyvalent metals (such as Mg and Al) was explained by Fabian and Sarma by considering the unique details of the band structure where the SOC is enhanced, which is known as the "hot-spot" model 21,22 .…”
Section: Elliott Showedmentioning
confidence: 90%